2021
DOI: 10.3389/fphys.2021.784803
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 and HSP70 Families in Lateolabrax maculatus: Genome-Wide Identification, Molecular Characterization, and Expression Profiles in Response to Various Environmental Stressors

Abstract: Heat shock proteins (HSPs) are a large class of highly conserved chaperons, which play important roles in response to elevated temperature and other environmental stressors. In the present study, 5 HSP90 genes and 17 HSP70 genes were systematically characterized in spotted seabass (Lateolabrax maculatus). The evolutionary footprint of HSP genes was revealed via the analysis of phylogeny, chromosome location, and gene copy numbers. In addition, the gene structure features and the putative distribution of heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…With increasing temperature, almost all of these genes had significantly and continuously upregulated expression, and the number of DE HSP70 genes was clearly increased. Similar results have also been found in the L. maculatus and O. mykiss , in which most of the examined HSP70 genes showed significantly upregulated expression in different tissues after exposure to heat stress [ 18 , 22 ]. Moreover, four significantly upregulated HSP70 genes in both kidney and liver tissues were identified, hsp70 ( hspa1a ), hspa1b , hspa5 , and hspa8a.1 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…With increasing temperature, almost all of these genes had significantly and continuously upregulated expression, and the number of DE HSP70 genes was clearly increased. Similar results have also been found in the L. maculatus and O. mykiss , in which most of the examined HSP70 genes showed significantly upregulated expression in different tissues after exposure to heat stress [ 18 , 22 ]. Moreover, four significantly upregulated HSP70 genes in both kidney and liver tissues were identified, hsp70 ( hspa1a ), hspa1b , hspa5 , and hspa8a.1 .…”
Section: Discussionsupporting
confidence: 81%
“…Heat shock protein 70 (HSP70) gene family members are involved in various housekeeping and stress-related activities in all organisms from bacteria to mammals [ 36 , 37 ]. Due to their important roles, especially in enhancing the response of cells to various stress stimuli, the HSP70 gene family has been extensively studied in a variety of aquaculture species, including invertebrate [ 38 ], bivalve [ 39 ], and multiple teleost species [ 14 , 18 , 19 , 20 , 21 , 23 ]. Nevertheless, a systematic analysis of HSP70 genes in the turbot has been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under H120, the gene encoding the heat shock protein 86 (Hsp86), also known as Hsp90aa1, was annotated by Gene_4216. Numerous studies have revealed the Hsp90aa1 gene can be significantly upregulated in a tissue-specific and time-dependent manner after heat stress [71]. Moreover, our previous study also confirmed the important role of HSP70AA1 in dairy cattle [72].…”
Section: Differentially Expressed Novel Transcript Lengths For Genes ...supporting
confidence: 83%
“…Under H120, the gene encoding the heat shock protein 86 (Hsp86), also known as Hsp90aa1 , was annotated by Gene_4216 . Numerous studies have revealed the Hsp90aa1 gene can be significantly up-regulated in a tissue-specific and time-dependent manner after heat stress [ 71 ]. Moreover, our previous study also confirmed the important role of HSP70AA1 in dairy cattle [ 72 ].…”
Section: Resultsmentioning
confidence: 99%